Clinical use of oral antibiotics in the treatment of acne vulgaris: Safety and therapeutic efficacy (Research, Society and Development, 2023)
The objective of this study is to present the latest in terms of good quality scientific evidence on the clinical use of oral antibiotics in the treatment of acne vulgaris, monitoring whether there is proof of their efficacy and safety in patients. This is a narrative literature review, where the electronic databases Scielo, Pubmed and Lilacs were used, with evidence published in the last ten years. Know that systemic based treatment should be considered in the presence of inflammatory acne and those that are difficult to control. In this case, it may involve antibiotic therapy, where the drugs in this line have as a mechanism of action a suppression of P. acnes, increased addition and free circulation fatty acids. However, the prolonged use of antibiotics, regardless of their class, constitutes a risk factor for the appearance of antimicrobial resistance, evidencing the fact that improper prescriptions of oral antibiotics for the treatment of acne must be avoided, and also that in the need to adopt this therapy, it is to consider the most appropriate class for the patient's needs, avoiding misuse. With this, it is important for prescribed professionals to have a broad knowledge of the classes and mechanisms of action of these drugs, in order to promote evidence-based treatment. In addition, it is imperative that new clinical studies be carried out with greater methodological rigor, in order to verify the best choice of acne treatment in its different degrees, guaranteeing the efficacy and safety of the patient.